'Together in Work, but Alone at Heart': Insider Perspectives on the Mental Health of British Police Officers. (21st March 2018) - Turner, Tim; Jenkins, Molly
Abstract: This research explored the mental health of British police. Interviews with six officers, of varying rank, were conducted to explore the nature, prevalence and causes of mental health issues amongst colleagues. Data was analysed using Interpretative Phenomenological Analysis to draw out key themes. Results indicate that whilst mental health issues are pervasive amongst police, many avoid seeking help due to a culture of invincibility, and a fear of impeding their career progression. The cause of distress was principally attributed to organizational bureaucracy; the impact of exposure to trauma was consistently minimized. Participants were critical of formal support mechanisms, and felt the absence of social spaces at work impeded collegiate support, and caused feelings of isolation. Findings highlight the need for a cultural shift, at both an individual and organizational level. Education is needed to counter the stigma of psychological distress amongst officers. Furthermore, mechanisms of formal and informal support should be reviewed as a priority.